Impact of demographic characteristics and antihyperglycemic and cardiovascular drugs on the cardiorenal benefits of SGLT2 inhibitors in patients with type 2 diabetes mellitus: A protocol for systematic review and meta-analysis. Issue 47 (24th November 2021) - Chang, Rong; Liu, Shu-Yan; Zhao, Li-Min
Abstract : Supplemental Digital Content is available in the text Abstract: Background: It is unclear whether demographic characteristics and baseline use of hypoglycemic and cardiovascular drugs significantly affect the efficacy of sodium-glucose transporter 2 (SGLT2) inhibitors on cardiorenal outcomes in patients with type 2 diabetes mellitus (T2DM). Methods: Randomized trials assessing the efficacy of SGLT2 inhibitors on cardiorenal outcomes in adult patients with T2DM were included in analysis. Three endpoints of interest were major adverse cardiovascular events (MACE), hospitalization for heart failure or cardiovascular death (HHF or CV death), and kidney composite outcome (KCO). We performed random-effects meta-analysis using the aggregate data of hazard ratios (HRs) and 95% confidence intervals (CIs). Subgroup analyses were done according to 17 factors of interest, including 7 factors related to demographic characteristics and 10 related to baseline use of antihyperglycemic and cardiovascular drugs such as renin–angiotensin system (RAS) inhibitor. We conducted meta-regression analyses to calculate P values for subgroup differences. Results: Seven trials were included in this meta-analysis. Compared with placebo, SGLT2 inhibitors significantly lowered the risk of MACE (HR 0.90, 95% CI 0.84–0.97) regardless of demographic characteristics and baseline use of insulin, statin or ezetimibe, RAS inhibitor, beta-blocker, and diuretic (Psubgroup from 0.088–0.981); that of HHF or CV death (HR 0.78, 95% CI 0.71–0.85) regardless of demographic characteristics and baseline use of 10 antihyperglycemic and cardiovascular drugs (Psubgroup from 0.147–0.999); and that of KCO (HR 0.63, 95% CI 0.57–0.69) regardless of demographic characteristics and baseline use of statin or ezetimibe, RAS inhibitor, and diuretic (Psubgroup from 0.073–0.918). Conclusions: The cardiorenal benefits of SGLT2 inhibitors were consistent in a broad population of T2DM patients. The findings of this meta-analysis suggest that SGLT2 inhibitors should be recommended in T2DM patients for the prevention of cardiorenal events, regardless of various demographic characteristics and baseline use of various hypoglycemic and cardiovascular drugs.